2007
DOI: 10.1117/1.2753365
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo spectroscopic quantification of sunscreen efficacy: proposal of a universal sun protection factor

Abstract: The sun protection factor (SPF) describes the protective behavior of sunscreens insufficiently, because this factor takes into account only the UVB spectral range, and strains the volunteers during its determination by invasively invoking an erythema. A new noninvasive method is proposed that is based on the UV spectroscopic measurement of tape strips taken from a sunscreen-treated skin area. The resulting sum transmission spectra of the tape strips reflect the in-vivo distribution of the absorber on the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…The specific number was determined taking the difference of the actual sum absorbance to the absorbance of tape 1 as a measure of the percentage filter amount obtained up to the selected tape number [13]. In the sum transmission spectra, the area under the curve in the UVA (320–400 nm) and UVB range (280–320 nm) was determined (UV WinLab version 2.70.01 software; PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific number was determined taking the difference of the actual sum absorbance to the absorbance of tape 1 as a measure of the percentage filter amount obtained up to the selected tape number [13]. In the sum transmission spectra, the area under the curve in the UVA (320–400 nm) and UVB range (280–320 nm) was determined (UV WinLab version 2.70.01 software; PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%
“…Tape stripping in combination with spectroscopic measurements is a well-established method to overcome the difficulties that arise with SPF determinations [13,14]. It has been demonstrated that the mean values of the average sum transmission in the UVB range correlate to the SPF at a high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The rough surface profile of the skin substantially reduces the efficiency and SPF of sun care products [22,28,29]. Active filters accumulate in the furrows and wrinkles of the skin and due to their inhomogeneous distribution reduce the UV absorption capacity by a factor of up to 10 [11].…”
Section: Discussionmentioning
confidence: 99%
“…This approved, minimally invasive method enables the penetration, secretion and reservoir properties of endogenous or topically applied substances in the stratum corneum of the skin to be studied under in vivo conditions. Inter alia, this method has been used previously to investigate UV filter characteristics and external influences on sunscreen behavior and efficiency [11,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on different mechanisms, several authors have proposed new methods to determine sunscreen efficacy in a more comprehensive manner [9,10,11], inter alia, the universal SPF (USPF) [12] and the radical formation ratio (RF) [13], which is based on electron paramagnetic resonance (EPR) measurements.…”
Section: Introductionmentioning
confidence: 99%